Building a digital economy in the post-Soviet states through the prism of international experience - Golubev, Sergey G. (Journal of the Belarusian State University. Sociology, 2019)
The report discusses the global trends of scientific and technological development; information and communication technologies as a key factor in the development of the sixth technological order; development of artificial intelligence systems, acting as a fundamental component of information and communication technologies; issues of complex digitalization of post-Soviet economies as the most important element of improving their competitiveness.
Keywords: global trends; digital economy; technological structure; artificial intelligence; information and communication technology